2021
DOI: 10.1002/anie.202101732
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Pronged Pulmonary Gene Delivery Strategy: A Surface‐Modified Fullerene Nanoparticle and a Hypotonic Vehicle

Abstract: Inhaled gene therapy poses a unique potential of curing chronic lung diseases, which are currently managed primarily by symptomatic treatments. However, it has been challenging to achieve therapeutically relevant gene transfer efficacy in the lung due to the presence of numerous biological delivery barriers. Here, we introduce a simple approach that overcomes both extracellular and cellular barriers to enhance gene transfer efficacy in the lung in vivo. We endowed tetra(piperazino)fullerene epoxide (TPFE)‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Furthermore, nonadhesive surface F127 coating enhances lung retention of our formulation by minimizing the adhesive interactions with airway mucus and lung‐resident macrophages 16–20 that promote the clearance of inhaled foreign matters from the lung as natural host defense mechanisms 11 . Of note, we have demonstrated that F127‐coated model NS formulations efficiently traverse human mucus samples harvested from various mucosal surfaces 31 and that covalent surface shielding of nanoparticles with the hydrophilic segment of F127 (i.e., polyethylene glycol) markedly reduces particle phagocytosis by alveolar macrophages 46 …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, nonadhesive surface F127 coating enhances lung retention of our formulation by minimizing the adhesive interactions with airway mucus and lung‐resident macrophages 16–20 that promote the clearance of inhaled foreign matters from the lung as natural host defense mechanisms 11 . Of note, we have demonstrated that F127‐coated model NS formulations efficiently traverse human mucus samples harvested from various mucosal surfaces 31 and that covalent surface shielding of nanoparticles with the hydrophilic segment of F127 (i.e., polyethylene glycol) markedly reduces particle phagocytosis by alveolar macrophages 46 …”
Section: Resultsmentioning
confidence: 90%
“…11 Of note, we have demonstrated that F127-coated model NS formulations efficiently traverse human mucus samples harvested from various mucosal surfaces 31 and that covalent surface shielding of nanoparticles with the hydrophilic segment of F127 (i.e., polyethylene glycol) markedly reduces particle phagocytosis by alveolar macrophages. 46 Albeit not primarily for inhaled use, there are more than 20 marketed NS products as of 2020. 45 On the other hand, aqueous drug suspensions are widely used in clinic for the inhaled treatment of patients with numerous lung diseases, including asthma, chronic obstructive pulmonary disease, and cystic fibrosis.…”
Section: In Vivo Therapeutic Efficacy Of Locally Administered Ntb-ns ...mentioning
confidence: 99%
“…To further enhance the gene editing efficiency in lung epithelium, NHEJ‐NP was prepared in a hypotonic aqueous solution, because previous studies demonstrated that a hypotonic shock could force cells to undergo intensive endocytosis and thus enhance the cellular uptake of nanoparticles via the osmotically‐driven regulatory volume decrease mechanism. [ 16 ] It was found that hypotonic NHEJ‐NP led to significant enhancement of the tdTomato fluorescence intensity in comparison with the PBS‐treated group (Figure 4C). Consistent with the IVIS results, more tdTomato expression was found in the hypotonic NHEJ‐NP‐treated lung epithelium than the isotonic NHEJ‐NP‐treated one (Figure 4D).…”
Section: Nhej‐np‐edited Mouse Lungs After Intratracheal Injectionmentioning
confidence: 96%
“…Shu, Suk, and coworkers investigate localized gene therapy via inhalation to treat refractory lung diseases ( Figure 17 ) [ 172 ]. This is advantageous in mitigating risks of systemic adverse effects caused by extra-pulmonary gene transfer.…”
Section: Biomedical Fullerene Nanoparticlesmentioning
confidence: 99%